Title – Using ‘Socialization Programme for Visually Impaired students’ (SPVI) to improve their Social Skills - Uplane, Megha; Wadegaonkar, Ashwini (Advances in Social Sciences Research Journal, 2017)
The purpose of this study was to investigate the effect of Socialization Program on nine participants with visual impairments. Socialization Programme for Visually Impaired (SPVI) was developed and then experiment was conducted to find out effectiveness of the programme on socialization of visually impaired male students of age 13-15 years. Findings from this study demonstrate that participants’ overall social skills were improved when assessed using tool ‘Social Skills Scale for Visually Impaired’ (SSSVI). The students demonstrated that the programme was effective for improving selected social skills for the participants. Thus, the study concluded that the SPVI programme was found to be effective to improve social skills of VI in all the skills viz. Taking Initiative, Maintaining Self-control, Accepting differences and Managing Emotions except the skill Expressing feelings. This study suggests future research is needed on the similar sample from the population and there is a need for more empirical research on the population’s social skills.